Doctor Who. Peter Capaldi [videorecording (DVD)] - Capaldi, Peter; Coleman, Jenna, 1986-; Mackie, Pearl, 1987-; Lucas, Matt, 1974- (BBC, 2018)
"The era of Twelfth Doctor Peter Capaldi is one of epic in the rich history of Doctor Who, and this enormous nine-disc collection contains every adventure. Join the Twelfth Doctor as he pilots the Tardis alongside companions Clara, Bill, and Nardole, encountering the mysterious River Song, the evil Missy, and a hoard of monsters including Daleks, Cybermen, Zygons, Ice Warriors, and many more ..."--Container